1987
DOI: 10.1021/j100311a026
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen atom reactions in the sonolysis of aqueous solutions

Abstract: Aqueous solutions of the spin trap 5,5-dimethylpyrroline TV-oxide (DMPO) and of Br2,12, Mn04~, AuCl4", and Ag+ were irradiated with 1-MHz ultrasound under argon-hydrogen mixtures of various compositions. DMPO was found to trap only very small amounts of hydrogen atoms while substantially greater amounts could be scavenged by the other solutes. The yield of H atoms as measured by the ESR signal of the DMPO adduct decreased with increasing H2 concentration in the gas mixture. The yields of the reduction products… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
89
1
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(94 citation statements)
references
References 0 publications
3
89
1
1
Order By: Relevance
“…It was observed that the presence of isopropanol has a crucial influence on the sonochemical reduction rate of AuCl − 4 ions. Without the additive, H ᭹ and ᭹ OH radicals would readily recombine to give a variety of products as shown in reaction [1] (27). Some other additives used in our investigation were also found to act as radical-scavenger and accelerator of the sonochemical reduction reaction.…”
Section: Sonochemical Process For the Formation Of Gold Nanoparticlesmentioning
confidence: 65%
“…It was observed that the presence of isopropanol has a crucial influence on the sonochemical reduction rate of AuCl − 4 ions. Without the additive, H ᭹ and ᭹ OH radicals would readily recombine to give a variety of products as shown in reaction [1] (27). Some other additives used in our investigation were also found to act as radical-scavenger and accelerator of the sonochemical reduction reaction.…”
Section: Sonochemical Process For the Formation Of Gold Nanoparticlesmentioning
confidence: 65%
“…Mason suggested a fourth site originating from a two site model that considers a liquid phase surrounding the hot bubble, that can either be a heated shell of liquid around the collapsing bubble or liquid droplets injected into the bubble by instabilities at the surface [100]. Of these sites the interfacial region is the greatest area of •OH population and recombination [20,30,[105][106][107][108][109][110]. Merouani et al through numerical simulation determined that of the numerous products, H 2 occurred most abundantly and more readily in the gas phase via reaction (8) [111].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…,H þ OH À /H 2 O þ e aq (11.2) Gutiérrez et al were able to reduce Tl þ in aqueous solutions using the hydrated electron to form colloidal thallium nanoparticles [7]. Metal ion/complex reduction reactions making use of the sonolytically produced hydrated electrons have only received limited attention [8].…”
Section: Metal Particlesmentioning
confidence: 99%